Regulatory Proposals for the Insertion of Distributed Energy Resources based on a Brazilian Utility Case and International Experiences - Rico, Julieta; Pelegia, Erick; Amado, Nilton; Bassi, Welson; Sauer, Ildo (International Journal of Energy Economics and Policy, 2023)
Utilities, policymakers, regulators, free market, and prosumers share a common interest in understanding whether benefits associated with such increased of DERs outweigh costs. To dimension and qualify B/C relationship, there are intrinsic variables relative to DERs' technical-economic arrangement and standard mechanisms used for its compensation: NEM, feed-in policies, etc. Other side, DERs must be adjusted on established regulatory framework, tariff schemes and utility revenue models. In this article, these three ambits are analyzed including a Brazilian southeastern region user's case study connected to MV network with DG measured data. Thus, some guidelines are pointed for the comprehensive implementation of DERs from the perspective of those involved.